ANALISIS PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DAERAH (APBD) BERBASIS KINERJA DI SKPD PROVINSI BENGKULU - Indra, Yetti Afrida (Institut Agama Islam Bengkulu, 2018)
This study aims to examine empirically and analyze whether the performance-based Bengkulu Provincial SKPD budgeting is analyzed from the commitment factors of all organizational components, improving the administration system, sufficient resources, clear rewards and firm penalties / sanctions. This study uses questionnaires in data collection. The sampling method in this study was people who were directly involved in budgeting in the agency / work unit within the Bengkulu provincial governmentThe results of the first hypothesis study show that the performance-based budgeting has a significant effect on commitment. This identifies that high commitment will affect the success of performance-based budgeting. The second hypothesis shows that performance-based budgeting has a significant effect on the administration system. The results of the third hypothesis study show that performance-based budgeting does not affect resources. The results of the fourth hypothesis study that performance-based budgeting has no significant effect on rewards. For the fifth hypothesis shows that performance-based budgeting has a significant effect on sanctions